Botryoid odontogenic cyst: Report of case found in routine imaginological examinations and an update of the literature - Cunha, John Lennon Silva; Silva, Amanda Feitoza da; Silva, Joao Vitor Rocha; Fonte, Juliana Batista Melo da; Bezerra, Bruno Torres; Sousa, Sílvia Ferreira de; Albuquerque-Júnior, Ricardo Luiz Cavalcanti de (Journal of Oral Diagnosis, 2019)
Botryoid odontogenic cyst (BOC) is a rare variant of the lateral periodontal cyst (LPC). As the biological behavior of BOC is variable and the literature is limited to that of individual case reports, there is no accepted consensus on the best management strategy. A 43-year-old Caucasian male was referred to a private dental clinic for routine radiographic examination. Extraoral and intraoral evaluations revealed no alterations. Panoramic radiography, periapical radiography, and cone beam computed tomography revealed a well-circumscribed osteolytic lesion of 2.0 cm in diameter, extending from the region of teeth 33 to 35. The provisional diagnostic was odontogenic keratocyst or lateral periodontal cyst. Histological analysis of the incisional biopsy revealed multiple cystic cavities lined by a thin nonkeratinized epithelium, exhibiting focal plaque-like thickenings, surrounded by a dense fibrous capsule. The diagnosis was BOC. The purpose of this study was to critically analyze the clinical and radiologic features of BOC based on case reports and case series published in the literature from 1973 to 2018 and to add a new one from our files.